Improving Students’ Confidence in Speaking Skills Using Scripted Role Play at Yogyakarta Tourism Academy - Santoso, Ihsan Budi; Prasetyo, Sigit (Universitas Ahmad Dahlan, 2024)
The research aims to investigate the efficacy of scripted role play in boosting students' confidence in speaking English at Yogyakarta Tourism Academy, focusing on third-grade students. Additionally, the study seeks to identify and address obstacles hindering students' speaking practice. This is qualitative descriptive employing interviews, observations, and literature reviews to gather data. The finding shows that scripted role-play can enhance students' speaking skills holds broader implications for language education and instructional practices. It suggests that structured and scaffolded activities like scripted role-play offer valuable opportunities for targeted language practice within a supportive learning environment. This implies that lecturers can incorporate scripted role-play into their curriculum to provide students with focused speaking practice, particularly for pronunciation, fluency, and intonation. The scripted role-play fosters collaboration and active participation among students, so it can contribute to a communicative and interactive classroom environment. Finally, scripted role-play can build students' confidence by providing clear guidelines and achievable goals. Students' confidence might be increased by knowing what to anticipate in a role-play scenario. Their comfort level with the script increases along with their confidence in their language skills leading them to more casual talks. Indeed, pronunciation can present a daunting obstacle for language learners. Scripted role-playing is a useful method in language training. It offers a safe environment for students to hone their language abilities, particularly their pronunciation while boosting their self-esteem and getting them ready for interpersonal interactions in the real world. However, scripted roleplay offers a promising solution and avenue for advancement.